Playing for a Healthy Life: Integrating Mobile Exergames in Physical Education - Pablo Sotoca-Orgaz; Marta Arévalo-Baeza; José A. Navia (Behavioral Sciences)
This study aimed to promote a coherent pedagogical framework for integrating mobile exergames into physical education (PE) as a strategy to reduce sedentary behavior. The intervention was grounded in the game-based learning methodology, assessing the impact of exergame practice on the physical and mental well-being of prospective PE teachers. The Borg Rating of Perceived Exertion (RPE) scale and a mental effort scale were used to evaluate perceived exertion across various mini-games, measuring physical intensity, motor engagement, and mental effort with participation from 130 undergraduate students in Physical Activity and Sport Sciences. Additionally, the pedagogical and motivational aspects of the Active Arcade v3.11 video game were analyzed to support its future integration into secondary education PE classes. Participants reported high levels of motor engagement throughout the program, accompanied by moderate physical intensity. They also emphasized the user-friendly nature of these augmented reality exergames and expressed enjoyment during the sessions. The findings suggest that mobile exergames hold considerable potential for enhancing skill acquisition and fundamental motor skills while promoting healthy habits among students in PE classes.